Peranan Badan Usaha Milik Desa (Bumdes) Memberdayakan Masyarakat - Nova Ratna Sikin Rambe; Indra Muda; Armansyah Matondang (Universitas Medan Area, 2021)
Village Owned Enterprises is a village business entity managed by the community and village government in an effort to strengthen the village economy formed based on the needs and potential of the village. With the existence of Act No. 6 of Article 87 paragraph 1 of 2014 explains, the Village can establish a Village Owned Enterprises. The community hopes BUMDes can drive the village economy. Economic assets in the village must be fully managed by the villagers through the BUMDes program. In this research using qualitative descriptive method, Researchers get some data from the results of observations and interviews conducted in Bangai Village. The existence of BUMDes is undeniable to bring economic and social change. BUMDes contribution mainly in the form of Village Original Income, where the net profit of BUMDes is allocated for village income. Based on the results of research related to the role of Village Owned Enterprises (BUMDes) empowering the community in Bangai Village, Torgamba District, Labuhan Batu Selatan District concluded that Bangai Jaya BUMDes has been instrumental in empowering the economy of the village community especially the poor, the role of BUMDes empower the community through the business that provides equipment agriculture where payment can be paid in stages.